Schoology-based Blended Learning in Academic Writing Class during the COVID-19 Pandemic - Prihandoko, Lastika Ary (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
COVID-19 is a global disease that significantly impacts almost all fields, including education. The shift from face-to-face learning to blended learning during the COVID-19 pandemic requires technological devices to support the learning process. Therefore, this study aims to explore the application of Schoology as a learning management system in academic writing classes during the COVID-19 crisis. The sequential mixed method was applied in this study by analyzing the data qualitatively and quantitatively. All students in the academic writing class were selected as participants using a total sampling technique. The methods used to collect data are observation, interviews, and questionnaires. Furthermore, the research instrument consisted of guided interviews and closed questionnaires distributed using a google form. The technique used to analyze the data is descriptive qualitative, and quantitative analysis. The results showed that Schoology is beneficial to be infused with blended learning. The Schoology platform stimulates students who have adequate online learning readiness to experience their learning positively using Schoology-based blended learning. However, institutional interventions must be implemented to provide training to students to improve digital competence, strategies to become independent learners, and time management.